2017
DOI: 10.4067/s0717-73562017005000112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an east-west phenotypic variation in body height, body form and body mass among prehistoric hunter-gatherers of Patagonia and Tierra del Fuego, chile

Abstract: Fuego-Patagonia's marine and terrestrial groups were historically described as phenotypically distinct but, studies of these phenotypic differences have yet to be conducted. This study evaluates phenotypic variation in Fuego-Patagonia. Phenotypic disparities result from extrinsic and intrinsic factors and therefore can reveal differences in both long and short term adaptations as well as genetic differences. Fifty-one adults were assessed. A total of six post-cranial measurements were included: maximum length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 46 publications
1
15
0
2
Order By: Relevance
“…The chon‐gününa küne language family found among Terrestrial groups and the qawasqar‐yagan of Marine groups form distinctive, distantly‐related linguistic groups (Viegas Barros, 1994). Likewise, phenotypic comparisons between Marine and Terrestrial groups revealed significant differences (Alfonso‐Durruty et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chon‐gününa küne language family found among Terrestrial groups and the qawasqar‐yagan of Marine groups form distinctive, distantly‐related linguistic groups (Viegas Barros, 1994). Likewise, phenotypic comparisons between Marine and Terrestrial groups revealed significant differences (Alfonso‐Durruty et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Territories of the four major ethnic groups according to colonial‐era documents are also highlighted. Site locations from Alfonso‐Durruty et al (2017; 2016; 2015) and Ortíz‐Troncoso (1975).…”
Section: Individuals and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are no estimations or proxies of the expected area occupied by a group of Kawésqar people. Thus, we estimated a proxy by using available data of group mobility for Yagán people (Binford, 2001; Figure 1), another canoeists group from the western Patagonia with important phenotypical similarities (Alfonso-Durruty et al, 2017), cultural affinities and spatial/ecological overlaps with the Kawésqar tradition (e.g. Fiore and Butto, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, comparisons between SP hunter‐gatherers denote greater variability in lower (femoral and tibial lengths) than in upper (humeral and radial lengths) limb dimensions (Alfonso‐Durruty et al, 2017; Béguelin & Barrientos, 2006). However, statistically nonsignificant differences in brachial and crural indices were found within female and male SP individuals according to terrestrial and marine subsistence strategy, even though the former showed relatively larger upper and lower limb dimensions (Alfonso‐Durruty et al, 2017). Within human populations, variation in brachial and crural indices are largely due to differences in distal limb‐segment lengths (Holliday & Ruff, 2001).…”
Section: Introductionmentioning
confidence: 99%